Hacking APIs : breaking web application programming interfaces - Ball, Corey (Cybersecurity manager) (No Starch Press, 2022)
"Teaches how to penetration-test APIs, make APIs more secure, set up a streamlined API testing lab with Burp Suite and Postman, and master tools for reconnaissance, endpoint analysis, and fuzzing. Topics covered include REST and GraphQL APIs, API authentication mechanisms, vulnerabilities, and techniques for bypassing protections. Includes nine guided labs"--